Figurative Language in The Stone Roses Self-Titled Album: A Habitus Perspective - Rizky Roy Rizwaanshah; Deni Suswanto; Dian Nurrachman (Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines the use of figurative language—specifically metaphor, symbol, and personification—in five songs from The Stone Roses’ self-titled album (1989): “Bye Bye Badman,” “Waterfall,” “Made of Stone,” “This Is the One,” and “I Am the Resurrection.” Employing literary criticism as its methodological approach, the study classifies each figurative expression using Perrine’s (1992) framework and interprets its meaning within the lyrical context. To extend the analysis beyond textual description, the study also applies Bourdieu’s (1990) concept of habitus, which explains how repeated social experiences shape enduring ways of perceiving, thinking, and acting. This sociological perspective is relevant because figurative language not only conveys aesthetic meaning but also reflects socially embedded dispositions and collective experiences encoded in the lyrics. The findings reveal that metaphor is the dominant device, transforming emotional states such as resilience, confinement, and dominance into concrete imagery, while symbols broaden these meanings into representations of instability and authority, and personification portrays the surrounding environment as an active participant in emotional experience. Through the lens of habitus, these recurring figurative patterns represent textual expressions of resistance, social constraint, and aspirations for transformation, demonstrating how literary and sociological perspectives together provide a richer understanding of song lyrics.